KOMUNIKASI ANTAR PRIBADI ATLET DALAM PEMELIHARAAN HUBUNGAN PADA TIM OLAHRAGA BASKET PON JAWA TENGAH - Adi Saputro, Topo; Naryoso, Agus; Rahardjo, Turnomo (Interaksi Online, 2024)
The condition that occurred was that there was a problem with interpersonal communication within the Central Java PON men's basketball team. Because there are 5 Central Java PON men's basketball team players who are professional players, of the 15 spots for Central Java PON men's basketball team players, only 10 spots are available in the team even though in terms of ability there is not much difference between professional players and amateur players. . The main problem is that in the team, jealousy arises from the players who are being selected towards the 5 professional athletes who are favored by the coach, because they are always praised, while the coach is very harsh towards the players who are being selected, speaks in harsh language and tends to demean the athletes who are being selected,this reducing their mental health team. This makes athletes who are being selected try to strengthen communication so that they can provide mutual encouragement tofellow selected athletes. The aim of this research is to find out about maintaining relationships, the obstacles in maintaining relationships and the efforts made to overcome obstacles to maintaining relationships in the Central Java PON basketball team. This research was carried out using a qualitative descriptive type. The subjects in this research were athletes from the Central Java PON men's basketball team. Where the informants in this research were three key informants, namely from team management, coaches, professional athletes and athletes selected for men's basketball at PON Central Java. Data collection was carried out by in-depth interviews. Data analysis was carried out using qualitative data analysis. Maintaining relationships in the Central Java PON Men's 5x5 basketball sports team is carried out intimately by building harmonious relationships between coaches and players. Obstacles in maintaining relationships in the Men's 5x5 PON Central Java basketball team are personal problems such as boredom because at that time there was a Covid-19 pandemic, apart from that other personal problems are injury problems, family problems and romantic problems in individual players as well as a lack of players in socialize with fellow team mates. Efforts made by coaches to overcome obstacles to maintaining relationships within the Men's 5x5 Basketball Team PON Central Java, especially those related to the lack of development of players, are by providing additional training according to the players' needs, being given the opportunity to play well during training, friendly matches and championships as well as Players are given compensation in the form of rest time so that players can be fit to take part in the championship